51 Years of India-Bangladesh Bilateral Relations: Opportunities and Challenges - Md Akbor Ali (Journal of Asian Social Science Research, 2023)
Because of their distinct histories, India and Bangladesh have unique neighbourly relations. India and Bangladesh have completed 51 years of bilateral ties in 2022, beginning in December 1971 with India's recognition of the newly independent People's Republic of Bangladesh. India played a significant role in the formation of Bangladesh during a liberation conflict with Pakistan. There are many things that tie the two nations together, such as a shared history and legacy, linguistic and social ties, and a love of art that reflects the diversity of human expression in music, literature, and other forms. Bangladesh is a geopolitically and strategically important country in India's neighbourhood policy. Bangladesh is especially important to India because of its connectivity with the country's seven landlocked northern sister states. Bangladesh's foreign policy discourse is dominated by the words "Indian factor" and "blocked by India." As a result, India is a top priority for Bangladeshi policymakers. The India-Bangladesh partnership affects millions of people in both countries, as well as in South Asia and beyond. The two nations are presently setting an example in South Asian politics in terms of security cooperation, connectivity, collaboration in the energy and power sectors, social and cultural integration, and bilateral trade. During the COVID-19 period, cooperation between the two nations was crucial. India made a humanitarian gesture at the time by assisting Bangladesh in developing its own vaccine. For more than 51 years, India and Bangladesh have had a more or less friendly relationship. There have been a few tense moments in the relationship's half-century history, most notably during the military regime and the BNP's rule. The golden jubilee year of the bilateral relationship was completed in 2021. The current research aims to provide a beneficial road map for the future by evaluating the history of the bilateral relationship and commenting on the problems and barriers experienced.